Dissociating Roles for the Nucleus Accumbens Core and Shell in Priming-, Cue-, and Stress-Induced Reinstatement of Food-Seeking Behavior - Lin, Peagan (Wake Forest University, 2013)
Many people who relapse to previous unhealthy eating habits after a period of abstinence from unhealthy foods report that relapse was triggered by re-exposure to palatable foods acting as a prime, exposure to food-associated cues, or exposure to stress. Dietary relapse can be studied using an animal reinstatement model, and research has found that this operant responding behavior for rewards is differentially affected by manipulation of the nucleus accumbens subregions, the core and shell. To determine if the nucleus accumbens core and shell uniquely contribute to the reinstatement of food-seeking, the present studies assessed the behavioral effects that resulted from inactivation of the core or shell on priming-, cue-, and stress-induced reinstatement of food-seeking. Results show that inactivation of both the core and shell blocked priming-induced reinstatement without dissociable effects. Inactivation of the core and shell also blocked cue-induced reinstatement, and there was evidence that the core and shell do have differential roles in cue-induced reinstatement, as inactivation of the shell on the first test day reduced responding on the second test day, when the shell was not inactivated. This finding suggests that the core plays a significant role in mediating motivational consequences of stimuli-outcome devaluation. Yohimbine, while a reportedly robust pharmacological stressor, was ineffective at inducing reinstatement in the current stress-induced reinstatement experiments. Taken together, the results of these thesis experiments indicate that the nucleus accumbens is a final common pathway of priming- and cue-induced reinstatement of food-seeking behavior and that the core and shell differentially mediate reinstatement behaviors depending on the relapse trigger.
Keywords: core; food; nucleus accumbens; reinstatement; shell